Conspiracy theories and social movements studies: A research agenda. Issue 12 (2nd November 2021) - Bertuzzi, Niccolò
Abstract: It is surprising to note the scarcity of contributions in social movement literature related to so‐called conspiracy theories. A considerable amount of the work on these topics has been produced in political science, history, media studies, social psychology and other disciplines. These accounts have often adopted a stigmatizing approach, looking at conspiracy theories as forms of pathologies (whether psychological, social or political). Moving from such a perspective to a constructivist one, I argue that conspiracy theories should represent an object of interest for social movement scholars: conspiracies supporters go into the streets to highlight their issues, protest against authority, propose alternative lifestyles and often claim to look for a better/different society. Applying the social movements toolkit can allow to better understand this phenomenon and apply critical perspectives in a more effective manner. On the basis of this premise, the first part of this article reviews the existing literature on conspiracy theories, also identifying the main lacunae; the second part outlines some possible research questions and lines of inquiry, moving beyond the classical theories in the field of social movement studies. The paper also introduces a number of new concepts, such as conspiracy mobilizations and conspiracy coalitions.